“Affective Maps”: MUME and Memory Park as Critical Matrixes for the Artistic Representation of the Past (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The so–called “affective turn” has irrupted into the field of humanities and social sciences forcing the revision of certain key con- cepts, such as agency, space, representation and temporality. Regarded as a matrix that insists on the performative, connective and unstable qualities of the affective dimension (Ahmed, 2004; Sedgwick, 2003; Ticineto Clough, 2007), such framework implies the revision of the way in which the reader/actor constitutes him/herself through that dimension. From these fundamentals, the pur- pose of this work is to analyze two spaces of memory created as artistic representations of the so–called traumatic or disruptive pasts: the Park of Memory in Buenos Aires and the Memory Museum located in Montevideo. A comparison of the two allows us to challenge the notion of “archive of feelings” (Cvetkovich, 2003) to propose that of “affective maps” instead, not only because of its theoretical fundamentals, but also because of its political consequences.
Keywords: Memory; Representation; Affects; Space.